Reading success for all students : using formative assessment to guide instruction and intervention - Gunning, Thomas G. (Jossey-Bass teacher., 2012)
"Help for reading teachers in continuous monitoring, assessment and instruction that targets students' problem areas This vital resource offers classroom teachers and literacy coaches practical assessments that can be used to evaluate key areas in students' reading performance. These assessments will provide information that can be directly used for planning instruction. Specific instructional techniques and activities are linked to each of the assessments so that teachers know exactly how to teach necessary skills. Tests and other evaluative devices are aligned with Common Core State Standards and state frameworks. Offers a proven model for monitoring and assessing students Assessments and instructional strategies are easy to implement as part of any curriculum Practical strategies are modeled on a tested approach for helping students work through their problem areas "--Provided by publisher.